Construction of a troublemaking risk assessment tool for patients with severe mental disorders in community of China - Shiming Li; Jieyun Yin; Queping Yang; Yingying Ji; Haohao Zhu; Qitao Yin (Scientific Reports)
Abstract Objective Construction a troublemaking risk assessment tool to predict the risk of troublemaking for patients with severe mental disorders in the community of China. Methods 28,000 cases registered in the Jiangsu Provincial Severe Mental Disorder Management System from January 2017 to December 2019 were collected. The risk factors of troublemaking among patients with severe mental disorders in the community were analyzed through Logistic regression analysis, then the troublemaking risk assessment tool was established and verified. Results The incidence of troublemaking among patients with severe mental disorders in the community was 7.15%. The results of multivariate logistic regression analysis showed that males, ≤ 44 years old, duration of disease ≤ 14 years, high school education and below, unemployed, subsistence allowances, schizophrenia, major symptoms > 1, psychiatric visits ≥ 1 time per year, unwilling to participate in community management and community rehabilitation activities, and delayed diagnosis < 2 months were risk factors for troublemaking. The above factors were incorporated into the nomogram model, and the area under the ROC curve of the nomogram model was 0.688 (95%CI: 0.563–0.726). The calibration curve proved that the probability predicted by the model was in good agreement with the actual probability. Conclusion The established troublemaking risk assessment tool for patients with severe mental disorders in the community based on Logistic regression analysis had good predictive performance, which could be applied to assess the probability of troublemaking among patients with severe mental disorders in the community.